2013
DOI: 10.1186/1471-2407-13-510
|View full text |Cite
|
Sign up to set email alerts
|

Common low-penetrance risk variants associated with breast cancer in Polish women

Abstract: BackgroundBreast cancer is the most common type of cancer and the second leading cause of cancer-death among women in Poland. The known high-risk mutations account for 25% of familial aggregation cases and 5% of total breast cancer predisposition. Genome-wide association studies have identified a number of common low-penetrance genetic variants, but their contribution to disease risk differs between populations.MethodsTo verify selected associations with breast cancer susceptibility among Polish women, the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…In fact it has been reported that the GA and/or AA genotypes of rs2736098 are associated with a decreased risk of head and neck (9) and breast (24,25) tumors. However, rs2736098 has been mostly associated with an increased risk for a variety of malignancies especially lung cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…In fact it has been reported that the GA and/or AA genotypes of rs2736098 are associated with a decreased risk of head and neck (9) and breast (24,25) tumors. However, rs2736098 has been mostly associated with an increased risk for a variety of malignancies especially lung cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Ledwoń et al. 15 reported a similar result in Polish women (OR = 1.31, 95% CI: 1.17–1.45). In contrast, Bayraktar et al.…”
Section: Introductionmentioning
confidence: 65%
“…Notably, the -1306 T-allele frequency differs across ethnicities: Saudi (0.10), Chinese (0.12), Brazilian (0.18), Greek (0.18), Australian (0.24), Polish (0.24), Mexican (0.26), Swedish (0.26) (Grieu et al 2004;Zhou et al 2004;Lei et al 2007;Roehe et al 2007;Delgado-Enciso et al 2008;Beeghly-Fadiel et al 2009;Ledwoń et al 2013;Saeed et al 2013a;Zagouri et al 2013). However, when subgroup analysis by ethnicity was performed, we could only find that CC was associated with a significant increase in breast susceptibility among Latin-Americans in the dominant model and the association disappeared in other models.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 9 case-control studies were eligible Lei et al 2007;Roehe et al 2007;DelgadoEnciso et al 2008;Beeghly-Fadiel et al 2009;Ledwoń et al 2013;Saeed et al 2013a;Slattery et al 2013;Zagouri et al 2013). The flow chart of study selection is shown in Figure 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation